Response of Winter Wheat (Triticum aestivum L.) to Fertilizers with Nitrogen-Transformation Inhibitors and Timing of Their Application under Field Conditions - Marie Školníková; Petr Škarpa; Pavel Ryant; Zdenka Kozáková; Jiří Antošovský (Agronomy, 2022)
Winter wheat is a widely cultivated crop that requires high inputs of nitrogen (N) fertilization, which is often connected with N losses. The application of fertilizers with nitrification (NI) and urease inhibitors (UI) is an opportunity to eliminate the risk of N losses and improve N availability to plants. The aim of this study is to compare the effect of conventional nitrogen fertilizers with fertilizers containing nitrogen-transformation inhibitors as well as to evaluate the timing of their application on the wheat-grain yield and quality under the conditions of a three-year field experiment. The examined fertilizers with inhibitors were applied in a single dose or in a split application in combination with conventional fertilizers. The single application of urea with NI and/or UI resulted in a relatively average increase in the grain yield, while protein content and the Zeleny-test values were significantly increased compared to the split N application. The more significant effect of urea with NI and UI was found under the moisture-rich conditions compared to the drier conditions. A significant increase in the grain yield (by 6.3%) and in the Zeleny-test value (by 16.5%) was observed after inhibited urea application comparing to the control treatment (without inhibitors).